Opinion 2457: Scarabaeus gazella Fabricius, 1787 (currently Digitonthophagus gazella or Onthophagus gazella; Insecta, Coleoptera, Scarabaeidae): neotype designated - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has used its plenary power to conserve the specific name of Scarabaeus gazella Fabricius, 1787 by designating a neotype.
Keywords: Nomenclature; taxonomy; Scarabaeidae; Scarabaeinae; Onthophagus; Digitonthophagus; Onthophagus gazella; dung beetle; Recent; Afrotropical; biological control of dung; pasture improvement